Pengaruh Pembuatan Rocket Stove Terhadap Pemberdayaan Masyarakat Dalam Pengelolaan Sampah Di Desa Tanjung - Dwi; Najwa; Ningrum (Yayasan Cendekia Gagayunan Indonesia, 2026)
Waste management in rural areas is often dominated by open burning practices due to limited access to environmentally friendly technologies. Desa Tanjung faces similar challenges, where household waste is commonly burned without proper treatment. This community service activity aimed to analyze the influence of rocket stove construction on community empowerment in household waste management in Desa Tanjung. A community-based participatory approach with a qualitative descriptive method was applied, involving local communities in the stages of planning, implementation, and evaluation. The findings indicate that the rocket stove effectively enables controlled combustion of dry organic waste with reduced smoke emissions and produces ash residues of approximately 1–5%, which can be utilized as plant fertilizer. Moreover, the program contributed to increased community participation, strengthened collective action through mutual cooperation, and encouraged behavioral changes in perceiving waste as a useful resource. The involvement of local waste management officers also fostered the emergence of local leaders in managing household waste. These results suggest that the implementation of appropriate technology such as a rocket stove not only provides technical solutions but also supports community empowerment and initiates social transformation toward sustainable waste management practices